Penerapan Konsep Komunikasi Partisipatif pada Pembangunan di Indonesia - Irma Yusriani Simamora; Miko Miko; Resty Resty; Anur Anur; Tazwa Tazwa; Siska Siska; Nadia Nadia; Manda Manda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Communication as a process of conveying information which contains persuasive messages. In development, communication is used to disseminate ideas, ideas and programs or policies from the government. Community empowerment is part of development communication that aims to improve the quality of life of the community. Communities need to be given space to participate actively in development by understanding what the problems are, finding solutions and making decisions wisely. This research has a role to know the concept of participatory communication in development communication. The method used is qualitative research through literature study, namely with a content approach and carried out by data collection techniques using books, journals and internet browsing.